Resilience response to yellow leaf curl disease and identification of resistance gene analogs (RGA) in pepper (Capsicum annuum) - Dyan Kusumaning Ayu; Awang Maharijaya; Muhamad Syukur; Sri Hendrastuti Hidayat (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ayu DK, Maharijaya A, Syukur M, Hidayat SH. 2021. Resilience response to yellow leaf curl disease and identification of resistance gene analogs (RGA) in pepper (Capsicum annuum). Biodiversitas 22: 4731-4739. Pepper yellow leaf curl disease (PYLCD) caused by infection of Begomovirus is a serious threat to pepper production worldwide. Identification of the resistance gene analogs (RGA) and resilience response of pepper against PYLCD is needed especially for selection resistance genotype. Evaluation of resistance response involving 28 pepper genotypes was carried out through transmission of Begomovirus using whitefly (Bemisia tabaci) as vector. The result showed that IPB C12 and F4-012328-6-3 were potential resistance genotypes. A total of 15 R gene analogs (CaRGA) containing NBS motif, namely CARGA1 to CARGA15, were identified by degenerated PCR amplification and database mining. The alignment of deduced amino acid sequence revealed conservation of subdomains Ploop (GKTT), kinase2 (LVVLDDV), RNBSB/kinase3 (IILTTR) and GLPL. BLASTp analysis indicated that 15 RGA showed high homology at deduced amino acid level with R gene identified such as whitefly resistance protein Mi-1.2, Pvr 9 gene for potyvirus, Begomovirus resistance protein, TRGA15 and RGA 13 for putative late blight resistance. Phylogenetic analysis exhibited that isolated sequences distinguished into CNL-NBS groups. These pepper RGA could be considered as candidate sequences of resistance genes.